2019
DOI: 10.1016/j.bpj.2018.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Material Properties of Wild-Type and Tectb−/− Tectorial Membranes

Abstract: The tectorial membrane (TM) is an extracellular matrix that is directly coupled with the mechanoelectrical receptors responsible for sensory transduction and amplification. As such, the TM is often hypothesized to play a key role in the remarkable sensory abilities of the mammalian cochlea. Genetic studies targeting TM proteins have shown that changes in TM structure dramatically affect cochlear function in mice. Precise information about the mechanical properties of the TMs of wild-type and mutant mice at aud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…G tm and η tm are material properties that have been directly reported by Lemons et al . 55 and other previous studies 17,42,56 for the TM of the mouse cochlea. These parameters have values ( G tm ≈ 5 kPa at the 20 kHz location and η tm = 0.03 Pa · s) that are lower than reported by Lemons et al .…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…G tm and η tm are material properties that have been directly reported by Lemons et al . 55 and other previous studies 17,42,56 for the TM of the mouse cochlea. These parameters have values ( G tm ≈ 5 kPa at the 20 kHz location and η tm = 0.03 Pa · s) that are lower than reported by Lemons et al .…”
Section: Discussionmentioning
confidence: 61%
“…Similarly, the occurrence of SOAEs is significantly increased in the Ceacam16 KO mice 36 ; while the mechanical properties of the TM of Ceacam16 KO mice have not been characterized, our theoretical results suggest that the enhancement of SOAEs in Ceacam16 KO might also be due to a decreased viscosity and/or stiffness of the TM. Previous work has shown that the Tectb KO mutation primarily affects the shear viscosity of the TM, which is about 50% lower than its value in WT TMs 42,55 . Our model predicts that if the mutation only affects the TM shear modulus, Tectb KO mice should emit slightly more SOAEs than WT mice, which is consistent with measurements by Cheatham et al .…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations